Do Natural T Regulatory Cells become Activated to Antigen Specific T Regulatory Cells in Transplantation and in Autoimmunity? - Hall, Bruce M.; Tran, giang T.; Verma, Nirupama; Plain, Karren; Robinson, Catherine M.; Nomura, Masaru; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2013)
Antigen specific Treg are often CD4+CD25+FoxP3+T cells, with a phenotype similar to natural Treg (nTreg). It is assumed that nTreg cannot develop into an antigen specific Treg as repeated culture with IL-2 and a specific antigen does not increase the capacity or potency of nTreg to promote immune tolerance or suppress in vitro. This has led to an assumption that antigen specific Treg mainly develop from CD4+CD25-FoxP3- T cells, by activation with antigen and TGF-beta in the absence of inflammatory cytokines such as IL-6 and IL-1. Our studies on antigen specific CD4+CD25+T cells from animals with tolerance to an allograft, identified that the antigen specific Treg were dividing, and needed continuous stimulation with specific antigen T cell derived cytokines. We identified that a variety of cytokines, especially IL-5 and IFN-γ but not IL-2 or IL-4 promoted survival of antigen specific CD4+CD25+FoxP3+ Treg. To examine if nTreg could be activated to antigen specific Treg, we activated nTreg in culture with either IL-2 or IL-4. Within three days, antigen specific Treg response emerged, and there is induction of new cytokine receptors on these cells. Specifically nTreg activated by IL-2 and antigen express the IFN-γ and IL-12p70 receptor but not the IL-5 receptor. These cells were responsive to IFN-γ or IL-12p70. nTreg activated by IL-4 and alloantigen express IL-5Rα not the IFNγ(IFNGR)or IL-12p70 receptor and become responsive to IL-5. These early activated antigen specific Treg, were respectively named Ts1 and Ts2 cells, as they depend on Th1 or Th2 responses. Further culture of Ts1 cells with Il-12p70 induces Th1-like Treg, expressing IFN−γ and T-bet as well as FoxP3. Our studies suggest that activation of nTreg with Th1 or Th2 responses, induced separate lineages of antigen specific Treg, that are dependent on late Th1 and Th2 cytokines, not the early cytokines IL-2 and IL-4.